Incorporation of digital information and communication technologies (TDIC) in the educational process: between challenges, expectations and possible paths to follow - Jesuz, Danilo Augusto Ferreira de; Pereira, Ana Lúcia (Revista Hipótese, 2019)
In this article we aim to analyze perceptions about Digital Information and Communication Technologies (TDIC) in the educational process. The research is qualitative in nature and the research subjects are postgraduate students in Education. Data were collected through questionnaires and organized through discourse analysis, from which it was possible to identify six categories. Our results point out that ICTs have the potential to contribute to the educational process, provided that the conception of instrumentalization and the educational model based on transmissivity are overcome, as well as the articulation between: Teacher education - Curriculum - Infrastructure.
Keywords: TDIC; Teaching; Learning; Teacher Training; Curriculum